Therapeutic Role of Retroperitoneal Lymphadenectomy in 170 Patients With Ovarian Clear Cell Cancer - Gao, Wen; Shi, Peipei; Sun, Haiyan; Xi, Meili; Tang, Wenbin; Yin, Sheng; Zhang, Jiarong (Frontiers in Oncology, 2022)
Introduction We evaluated the therapeutic role of retroperitoneal lymphadenectomy in patients with ovarian clear cell cancer (OCCC). Materials and Methods We retrospectively reviewed 170 OCCC patients diagnosed at two hospitals in China between April 2010 and August 2020. Clinical data were abstracted, and patients were followed until February 2021. Patients were divided into retroperitoneal lymphadenectomy and no lymphadenectomy groups. The Kaplan–Meier method was used to compare progression-free (PFS) and overall survival (OS) between the two groups. Statistical differences were determined by the log-rank test. The COX proportional hazards regression model was applied to identify predictors of tumor recurrence. Results The median age was 52 years; 90 (52.9%) and 80 (47.1%) patients were diagnosed as early and advanced stage, respectively. Clinically positive and negative nodes was found in 40 (23.5%) and 119 (70.0%) patients, respectively. Of all the 170 patients, 124 (72.9%) patients underwent retroperitoneal lymphadenectomy, while 46 (27.1%) did not. The estimated 2-year PFS and 5-year OS rates were 71.4% and 65.9% in the lymphadenectomy group, and 72.0% and 73.7% in no lymphadenectomy group (p = 0.566 and 0.669, respectively). There was also no difference in survival between the two groups when subgroup analysis was performed stratified by early and advanced stage, or in patients with clinically negative nodes. Multivariate analysis showed that retroperitoneal lymphadenectomy were not an independent predictor of tumor recurrence. Conclusion Retroperitoneal lymphadenectomy provided no survival benefit in patients diagnosed with OCCC. A prospective clinical trial is needed to confirm the present results.